2006
DOI: 10.1007/s00299-006-0255-x
|View full text |Cite
|
Sign up to set email alerts
|

Genes up-regulated during red coloration in UV-B irradiated lettuce leaves

Abstract: Molecular analysis of gene expression differences between green and red lettuce leaves was performed using the SSH method. BlastX comparisons of subtractive expressed sequence tags (ESTs) indicated that 7.6% of clones encoded enzymes involved in secondary metabolism. Such clones had a particularly high abundance of flavonoid-metabolism proteins (6.5%). Following SSH, 566 clones were rescreened for differential gene expression using dot-blot hybridization. Of these, 53 were found to overexpressed during red col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 32 publications
2
44
0
1
Order By: Relevance
“…This is in keeping with the observed reduction of kaempferol glycoside levels in the anthocyanin overaccumulator line (pap1-D; Tohge et al, 2005). In addition to the important roles of flavonoids and phenylpropanoids under light stress, nutrient conditions such as nitrogen, sulfur, and phosphorus deficiency as well as high-carbon stress can also cause anthocyanin synthesis (Do and Cormier, 1991;Rajendran et al, 1992;Bonguebartelsman and Phillips, 1995;Nooden et al, 1996;Stewart et al, 2001;Nikiforova et al, 2004;Park et al, 2007). Many studies concerning the relationship between nitrogen and the rate of CO 2 assimilation and photosynthesis have suggested that anthocyanin accumulation is a metabolic marker for carbon/nitrogen imbalance under such stress conditions (Smart, 1994;Zheng et al, 2009).…”
Section: Carbon-based Secondary Metabolites Under the Regulation Of Nmentioning
confidence: 53%
“…This is in keeping with the observed reduction of kaempferol glycoside levels in the anthocyanin overaccumulator line (pap1-D; Tohge et al, 2005). In addition to the important roles of flavonoids and phenylpropanoids under light stress, nutrient conditions such as nitrogen, sulfur, and phosphorus deficiency as well as high-carbon stress can also cause anthocyanin synthesis (Do and Cormier, 1991;Rajendran et al, 1992;Bonguebartelsman and Phillips, 1995;Nooden et al, 1996;Stewart et al, 2001;Nikiforova et al, 2004;Park et al, 2007). Many studies concerning the relationship between nitrogen and the rate of CO 2 assimilation and photosynthesis have suggested that anthocyanin accumulation is a metabolic marker for carbon/nitrogen imbalance under such stress conditions (Smart, 1994;Zheng et al, 2009).…”
Section: Carbon-based Secondary Metabolites Under the Regulation Of Nmentioning
confidence: 53%
“…Park et al (2007) isolated five fragments of the anthocyanin synthase gene, whose transcription coincided with plant color. However, the molecular mechanism of anthocyanin accumulation in lettuce is still unclear and gene transcription has a poor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet irradiation is known to increase the expression of anthocyanin biosynthetic genes in several plant species and also lead to an increase in the accumulation of anthocyanins [70,94]. Research examining the structure of the promoter sequences of two of the structural genes involved in flavonoid biosynthesis in grapes revealed that these genes could be induced by exposure to ultraviolet-A light [95,96].…”
Section: Factors Affecting Variation In Anthocyaninsmentioning
confidence: 98%